Figurations of the body in the narrative of Cheri Lewis G. - Pérez Cuadra, María del Carmen (2024)
Through a comparative reading exercise, and following an inductive method, this article identifies different ways of representing or imagining the body in a corpus of works by the Panamanian author Cheri Lewis G., observing the possible relationships, tensions or contradictions between this same type of fictional representation in the narra-tive works of other contemporary Central American authors. In the fictional worlds of the selection, on the one hand, the fragmented, animalized or hybridized body proposes ways to contradict, think, resistor criticize certain oppressive standards towards women; on the other, he makes metaphorical elaborations on human affective relationships with other forms of life, as well as allegories of the fragmented nation.